Summary of Newly Found Ants’ Cognitive Abilities, and Their Occurrence in Humans - Cammaerts, Marie-Claire; Cammaerts, Roger (Journal of Biology and Life Science, 2023)
Authors studied the cognitive abilities of the ant Myrmica sabuleti Meinert 1861, and in addition to the separate publications of their findings, they also summarized them in until now three papers. Here, the authors summarize their eight last findings, and report similar abilities in humans as well as advices for acquiring and using them. The ants can associate visual cues, numbers of elements, and odors with the time periods of their occurrence, and do so taking into account the characteristics of the elements. Humans should do so for ameliorating their daily life. For adding two numbers, the ants must see them with a time gap not exceeding 8 minutes. The ants discriminate recent and previously perceived events, locating the recent but not the old ones on a ‘time line’. Humans must learn to evaluate the passing time, to have a ‘time line’. The ants’ time perception is underestimated when they are more active. This is true for humans, and must be considered while working, playing or doing nothing (e.g., elderly persons). The ants can navigate using a learned (memorized) sequence of odors. Humans must learn sequences of cues for finding their way. The ants discriminate even and odd numbers until the number 7. Humans are sensitive to numbers’ parity, and this should freely impact their choice. Shortly, the authors revealed four cognitive abilities in ants which should occur in humans, natively or acquired through experiences, at a more precise, complex and extended level, in order to provide them with an as comfortable as possible live.